2020
DOI: 10.1007/s13312-020-1917-4
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Exclusive Human Milk Diet for All Babies in COVID-19 Times

Abstract: The coronavirus disease (COVID-19) pandemic has ramifications for the delivery of newborn nutrition and care services. World Health Organization recommends continuation of breastfeeding in these difficult times, with due precautions. If direct breastfeeding is not possible, milk expression should be explored. Pasteurized donor human milk from milk banks may be fed if mother's own milk is not available. To universalize access to human milk, the Indian government has proposed the establishment of comprehensive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
0
23
0
3
Order By: Relevance
“…The COVID-19 pandemic has posed several challenges to the provision of newborn nutrition and care interventions, including maternal support, breastfeeding, and family participatory care. Mothers and healthcare workers are confused and scared of COVID-19 and breastfeeding, along with a sense of heightened stigma about the disease which is impacting access to breastmilk [ 10 , 30 ]. Restrictions in lockdown made it difficult for mothers and families to get access to feeding support.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has posed several challenges to the provision of newborn nutrition and care interventions, including maternal support, breastfeeding, and family participatory care. Mothers and healthcare workers are confused and scared of COVID-19 and breastfeeding, along with a sense of heightened stigma about the disease which is impacting access to breastmilk [ 10 , 30 ]. Restrictions in lockdown made it difficult for mothers and families to get access to feeding support.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of research by Susan Narula, (2015) on the Relationship between Knowledge Level and Mother's Work with the Success of Lactation Techniques in Breastfeeding Mothers, it shows that most (80.4%) breastfeeding mothers fail to perform lactation techniques, (64.7%) breastfeeding mothers have a low level of knowledge and most (80.4%) breastfeeding mothers have jobs. The COVID-19 has ramifications for the delivery of newborn nutrition [11][12][13] . The factors that influence the process of breastfeeding mothers with infants aged 0-6 months, it is shown that 47% of mothers show poor breast conditions, 55% of mothers show poor breastfeeding techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the novelty of the pandemic, an implicit variability has to be accepted concerning what is advisable for monitoring early neonatal stages. A largely shared opinion considers essential the involvement of professionals with in-person visits either at home or within the health facilities and supports this mode in order to implement neonatal jaundice assessment by the mother and to plan for vaccinations ( Harriel et al., 2020 ; Royal College of Obstetricians and Gynaecologists, 2020b ; Sachdeva et al., 2020 ; Tscherning et al., 2020 ). On the other hand, a recent study supports the idea that maternal and child monitoring may be performed exploiting emerging virtual technologies in up to 87.3% of overall postpartum consultations whenever videoconferencing is available between institutions and homes.…”
Section: Discussionmentioning
confidence: 99%